Systematic review of catatonia treatment - Pelzer ACM (Neuropsychiatric Disease and Treatment, 2018)
Anne CM Pelzer,1 Frank MMA van der Heijden,2 Erik den Boer3 1Department of Psychiatry, Reinier van Arkel, ‘s-Hertogenbosch, 2Department of Psychiatry, Vincent van Gogh Institute for Psychiatry, Venlo, 3Department of Psychiatry, GGzE, Eindhoven, the Netherlands Objective: To investigate the evidence-based treatment of catatonia in adults. The secondary aim is to develop a treatment protocol. Materials and methods: A systematic review of published treatment articles (case series, cohort or randomized controlled studies) which examined the effects of particular interventions for catatonia and/or catatonic symptoms in adult populations and used valid outcome measures was performed. The articles for this review were selected by searching the electronic databases of the Cochrane Library, MEDLINE, EMBASE and PSYCHINFO. Results: Thirty-one articles met the inclusion criteria. Lorazepam and electroconvulsive therapy (ECT) proved to be the most investigated treatment interventions. The response percentages in Western studies varied between 66% and 100% for studies with lorazepam, while in Asian and Indian studies, they were 0% and 100%. For ECT, the response percentages are 59%–100%. There does not seem to be evidence for the use of antipsychotics in catatonic patients without any underlying psychotic disorder. Conclusion: Lorazepam and ECT are effective treatments for which clinical evidence is found in the literature. It is not possible to develop a treatment protocol because the evidence for catatonia management on the basis of the articles reviewed is limited. Stringent treatment studies on catatonia are warranted. Keywords: review, catatonia, therapeutics, electroconvulsive therapy, benzodiazepines, lorazepam, ECT